SISTEM INFORMASI MANAGEMEN DAN AKUNTANSI BARANG MILIK NEGARA DALAM PENERAPAN AKUNTANSI BERBASIS AKRUAL - Isti'anah Isti'anah (JURNAL INFORMASI, PERPAJAKAN, AKUNTANSI, DAN KEUANGAN PUBLIK, 2011)
One of mandate from Law No. 17/2003, which is one package of the State Finance Regulation, is the implementation of accrual accounting is believed to contain a better policy planning and a more informative approach to asset management. The reform of accounting practices in the government sector has strongly influenced property asset management. On a global scale, implementation of accrual basis as a way to bring the government believed to be more accountable and transparent in the use of resources and government policies in order to execute and perform the duties of State. Indonesia has implemented an asset management system of the State, namely Information Systems and Management of State Assets (SIMAK-BMN) which is part of the Agency Accounting System (SAI). SIMAK-BMN process acquisition of transaction, changes and removal of BMN to support Financial Accounting System (SAK) to Consolidated Balance Sheet. In addition, this system produces various reports, books, and cards that provide managerial information in the management of BMN. Administration activities and reporting of State Property by SIMAK-BMN is a standard in determining of value asset state which proper, correct and reliable. SIMAK - BMN besides supporting the implementation of the accountability, also provide various informations to the management public goods. One such issue is the relationship between accounting reform and asset management reform. This issue is a bundle of accounting issues: (1) how far should asset valuation on the balance sheet be pushed for real properties the government owns, (2) how does shifting to accrual-based accounting standards affect property accounting and management, and (3) how much importance should asset management policy attach to accounting rules?